Plant traits determining biogeomorphic landscape dynamics: A study on clonal expansion strategies driving cliff formation at marsh edges. Issue 10 (23rd August 2021) - Cao, Haobing; Zhu, Zhenchang; Herman, Peter M.J.; Temmerman, Stijn; de Smit, Jaco; Zhang, Liquan; Yuan, Lin; Bouma, Tjeerd J.
Abstract: Despite the well‐recognized importance of plant traits for biogeomorphic development of landscapes, our understanding remains limited of how species‐specific plant traits respond to and serve as drivers for the sedimentary dynamics within a biogeomorphic landscape. By manipulating a series of laboratory experiments, using mesocosms and a flume, we examined how species‐specific differences in expansion strategy, i.e., clonal step‐length of laterally expanding tillers, both respond to sediment type and drive cliff formation and persistence. We compared three marsh species, with contrasting clonal expansion traits, that are dominant in many estuaries worldwide: Spartina anglica, Scirpus maritimus, and Phragmites australis . Our results revealed that S. anglica tussocks tend to have high shoot density due to a short clonal expansion step‐length, whereas S. maritimus tussocks were much more diffuse and tend to have a longer clonal expansion step‐length. P. australis showed intermediate traits. Clonal expansion step‐length did show within‐species variation in response to sediment texture, but species‐specific differences remained the most important. Species with smaller clonal step‐lengths, such as S. anglica in this study, are more likely to induce cliffs at the marsh edge by driving formation of larger cliff heights and also having lower capacity to grow out from cliffs. Our findings thus illustrate how dynamic landscape features like cliffs at marsh edges depend on the clonal expansion traits of the dominant species. This enhances current understanding of the formation and development of marsh edges, and is instructive for understanding the role of species‐specific traits in driving distinct biogeomorphic landscape dynamics.